Vascular Inflammation and Cardiovascular Burden in Metastatic Breast Cancer Female Patients Receiving Hormonal Treatment and CDK 4/6 Inhibitors or Everolimus - Papageorgiou, Christos; Zagouri, Flora; Tampakis, Konstantinos; Georgakopoulou, Rebecca; Manios, Efstathios; Kafouris, Pavlos; Benetos, Georgios; Koutagiar, Iosif; Anagnostopoulos, Constantinos; Dimopoulos, Meletios A.; Toutouzas, Konstantinos (Frontiers in Cardiovascular Medicine, 2021)
Background: Chemotherapy regimens for breast cancer treatment can promote vascular dysfunction and lead to high cardiovascular risk. Purpose: To investigate the cardiovascular burden and vascular inflammation in metastatic breast cancer patients receiving CDK 4/6 inhibitors or everolimus in addition to standard hormonal treatment. Methods: 22 consecutive female patients with metastatic breast cancer were enrolled. Relative wall thickness (RWT) and left ventricle mass (LVM) measurements by transthoracic echocardiography were obtained followed by 24-h ambulatory blood pressure monitoring, and 18F-fluorodeoxyglucose positron-emission tomography/computed tomography imaging. Uptake of the radiotracer in the aortic wall was estimated as tissue-to-background ratio (TBR). Each patient was assessed for the aforementioned parameters before the initiation and after 6 months of treatment. Results: At follow up, patients assigned to CDK 4/6 treatment demonstrated increased 24-h systolic blood pressure (SBP) (p = 0.004), daytime SBP (p = 0.004) and night time SBP (p = 0.012) (Group effect). The 24-h mean arterial pressure measurements were also higher in CDK 4/6 population, in comparison to everolimus that displayed firm values (Group effect- p = 0.035, Interaction effect-p = 0.023). Additionally, 24 h diastolic blood pressure recordings in CDK 4/6 therapy were higher opposed to everolimus that remained consistent (Interaction effect- p = 0.010). In CDK 4/6 group, TBR aorta also increased significantly, whereas TBR values in everolimus remained stable (Interaction effect-p = 0.049). Both therapeutic regimens displayed statistically significant damaging effect to RWT and LVM. Conclusion: CDK 4/6 inhibitors and hormonal treatment can lead to increased vascular inflammation, and higher blood pressure compared to the combination of everolimus and hormonal treatment. Moreover, both treatment strategies promoted left ventricle remodeling.